Using Differentiated Instruction for Phase C Students’ Vocabulary Building at PKBM El Fataa Banyuwangi - Priscilla Era’in Laivigata; Wulan Wangi; Elin Widiyanti; Afnan Hafidz Nasrullah (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2026)
Vocabulary is a common difficulty faced by beginners. Differentiated instruction is a new innovation for teaching and learning strategy that can be highly relevant to vocabulary development. Preliminary findings showed that students’ average vocabulary score at PKBM El Fataa Banyuwangi was 69.5, which was below the minimum mastery criterion. Therefore, the researchers conducted Classroom Action Research using differentiated instruction to improve Phase C students’ vocabulary mastery. The method used in this research is classroom action research. This research used observation, documentation, and tests in collecting the data. The research was conducted in one cycle for two meetings and it consists of planning, acting, observing, and reflecting. The research result showed that all students (100%) of phase C students at PKBM El Fataa Banyuwangi have reached 75 and more score as the criteria of success. The average score was 82. The differentiated instruction used in this classroom action research is able to help students to improve their vocabulary building. This statement is supported by tutor and student observations, and student learning outcomes. The success of the implementation of differentiated instruction was indicated by the achievement of the criteria of success, as evidenced by the students’ test scores.